Conservatives versus wildcats : a sociology of financial conflict - Polillo, Simone, 1978- (Stanford University Press, 2013)
For decades, the banking industry seemed to be a Swiss watch, quietly ticking along. But the recent financial crisis hints at the true nature of this sector. As Simone Polillo reveals in Conservatives Versus Wildcats, conflict is a driving force. Conservative bankers strive to control money by allying themselves with political elites to restrict access to credit. Barriers to credit create social resistance, so rival bankers-wildcats-attempt to subvert the status quo by using money as a tool for breaking existing boundaries. For instance, wildcats may increase the circulatio.